Psychosocial Aspects of Mothers of Malnourished and Well-Nourished Children - Zein Sulaiman; M. A. Husaini; Joko Kartono; Rini Azwein Jenie; Sihadi Sihadi; Paul F. Matulessy; Darwin Karyadi (Indonesian Pediatric Society, 1996)
In order to determine whether differences in sociopsychological environÂment and related factors exist between malnourished and well-nourished children, a study on 126 underfive children was carried out in Bogor, West Java, Indonesia. The children were grouped into severely malnourished, mild-moderately malnourished, and well-nourished children. Each group consisted of 42 children, and they were selected from die same surrounding which have fairly same housing condition, age, and sex. Differences were found between the three groups on parent's education, the birth order of the child, the expenditure per capita, and breast feeding history. However, there was no significant difference on knowledge about health and nutrition, mother and child relationship. It was observed that children who were never breastfed had a tendency to be severely or moderately malnourished. The mothers who were doing only household chores were worried about the future of their children; on the other hand, the mothers who have more contact with community (monthly welfare movement meetings, and other activities outside homes) have a tendency to have well-nourished children. The proposed hypothesis that mother and child interaction affects the level of die nutritional status of the children requires more testing in a more comprehensive study.